Phenotypic and Genotypic Study of Antibiotics Resistance Profile in Escherichia coli Isolated from Broilers in Cianjur, Indonesia - Aprilia Hardiati; Safika; I Wayan Teguh Wibawan; Fachriyan Hasmi Pasaribu (Acta VETERINARIA Indonesiana, 2021)
This study aimed to investigate the phenotypic and genotypic of antibiotics resistance profile in Escherichia coli. The 30 samples come from cloacal swab of broilers in Cianjur, Indonesia. Isolation and identification of E. coli was performed by culture in McConkey agar, eosin methylene blue agar, Gram staining and five essential biochemical tests (IMViC). In this study, 10 isolates (33.3%) were confirmed E. coli positive. Phenotypic profile was performed by screening all isolates with 8 antibiotics of 6 antibiotic groups. The screening was carried by Kirby-Bauer disk diffusion method based on the standard of CLSI. For genotypic profile, each resistant isolate was detected antibiotic resistance-encoding gene. The result showed all isolates (100%) resistant against tetracyclin, oxytetracycline and erythromycin. Nine isolates (90%) detected nalidixic acid and enrofloxacin-resistant. The ciprofloxacin and gentamicin-resistant isolates were 70% and 40%, respectively. There was no resistant isolate for chloramphenicol. Multi drug-resistant was detected on 90% isolates. Only gyrA (100%) and tetA (80%) genes were detected. This study showed high rate of occurrence of antibiotic resistance in E. coli. Not all resistant isolates were detected in the antibiotic resistance-encoding gene in this study. Future research to detect resistance genes should use more varied target genes.